2019
DOI: 10.30874/comdev.2018.193
|View full text |Cite
|
Sign up to set email alerts
|

The Coaching Assistance of Preparing of Financial Statements based on SAK EMKM Integrated [Asistensi Pembinaan Penyusunan Laporan Keuangan Berbasis SAK EMKM yang Terintegrasi]

Abstract: The board of Indonesia Accounting Standard published SAK EMKM for effective per 1 January 2018. It is becoming the framework in preparing financial statements based EMKM. Its purpose is addressed to perpetrators of SMEs in order to be more comprehensive to prepare independently financial statements so the access to obtain the finance is easier. A workshop was conducted for 2 days in this community service. The perpetrators of SMEs did the practice of preparing statements based on business transaction integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Apart from that, the approach method that will be used in this service program includes participatory training and mentoring. Participatory training is carried out by involving the target audience as recipients of knowledge and understanding regarding the management of strengthening and improving the capabilities of human resources (HR) of Micro Business actors through the use of digital technology in preparing financial reports, as well as strengthening and improving the HR capabilities of Micro Business actors in digital-based marketing strategies using digital technology (Rayyani et al, 2018), (Violinda et al, 2022), (Haanurat et al, 2022), (Ahmad et al, 2021), (Zulfahri et al, 2022); (Purwana et al, 2017), as shown in Table 1.…”
Section: B Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from that, the approach method that will be used in this service program includes participatory training and mentoring. Participatory training is carried out by involving the target audience as recipients of knowledge and understanding regarding the management of strengthening and improving the capabilities of human resources (HR) of Micro Business actors through the use of digital technology in preparing financial reports, as well as strengthening and improving the HR capabilities of Micro Business actors in digital-based marketing strategies using digital technology (Rayyani et al, 2018), (Violinda et al, 2022), (Haanurat et al, 2022), (Ahmad et al, 2021), (Zulfahri et al, 2022); (Purwana et al, 2017), as shown in Table 1.…”
Section: B Methodsmentioning
confidence: 99%
“…These challenges include the lack of Trade Business License (SIUP) among many MSMEs, limited capital, insufficient knowledge of business operations, underutilization of digital marketing for sales improvement, inadequate understanding of business development, weak branding strategies, ineffective business communication, manual bookkeeping practices, limited innovation in production processes, and inadequate human resource management. Research references that address these issues include (Arijanto, 2021), (Rayyani et al, 2018), (Rayyani & Abdi, 2020), (Hendratmoko, 2021).…”
Section: A Introductionmentioning
confidence: 99%
“…Statements of financial status, an income statement, and other financial statements derived from SAK EMKM and the financial statements notes (Ardila et al, 2019 based financial accounting standards of Micro small entity (SAK EMKM) (Dwiantini et al, 2021). And also, The SMEs that committed the crimes practiced the act of creating financial statements based on commercial transactions that were connected with tax reporting (Rayyani et al, 2019). Other side by Purwanti & Fatmawati (2021) shows that SAK EMKM is various interpretations by MSMEs actors which some usefull and not.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of MSEs should be paid attention (Putri, 2022;Frihatni et al, 2022). They could contribute to the national income through tax (Rayyani et. al, 2019).…”
Section: Introductionmentioning
confidence: 99%